Association between oral JAK-1 inhibitors and infection risks in atopic dermatitis: a retrospective analysis of the FAERS database - Tang, Zenan; Mu, Zhanglei; Wang, Xiaojie; Zhao, Yan (Frontiers in Medicine, 2025)
BackgroundJanus kinase (JAK)-1 inhibitors have been approved for moderate-to-severe atopic dermatitis (AD). Despite favorable efficacy, their real-world infection risk profile requires further investigation.MethodsWe conducted a retrospective disproportionality analysis using the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database. Reports identifying upadacitinib or abrocitinib as primary suspect drugs for “Infections and Infestations” adverse events (AEs) in AD treatment from Q3 2019 to Q1 2025 were included. Four disproportionality methods were employed to detect infection-related safety signals.ResultsA total of 18 infection-related positive safety signals associated with abrocitinib were identified, which include known AEs (herpes zoster, eczema herpeticum, and herpes simplex) and unexpected signals (sepsis, appendicitis, and septic shock). Upadacitinib showed 64 infection-related signals, encompassing known AEs (herpes zoster, pneumonia, and influenza) and unexpected signals (sepsis, appendicitis, and septic shock). Herpes zoster was the most frequent infection-related AE for both drugs.ConclusionThis study confirms established infection risks of JAK-1 inhibitors in AD (particularly herpes zoster) and identifies novel potential safety signals (sepsis, appendicitis, and septic shock). These findings provide real-world insights into the risk of infections associated with JAK inhibitors.